The Shaping of Peace : Canada and the Search for World Order, 1943-1957 (Volume 2). - Holmes, John, W. (Heritage., 1982)
This volume is concerned with the developments in the decade after the war, with the changing Canadian concepts as they were shaped by events and challenges.